Valorisation of hydrothermal liquefaction wastewater in agriculture: effects on tobacco plants and rhizosphere microbiota - Gugliucci, Wanda; Cirillo, Valerio; Maggio, Albino; Romano, Ida; Ventorino, Valeria; Pepe, Olimpia (Frontiers in Plant Science, 2023)
Industrial wastewater obtained from hydrothermal liquefaction (HTL-WW) of food wastes for biofuels production could represent a source of crop nutrients since it is characterized by a high amount of organic and inorganic compounds. In the present work, the potential use of HTL-WW as irrigation water for industrial crops was investigated. The composition of the HTL-WW was rich in nitrogen, phosphorus, and potassium with high level of organic carbon. A pot experiment with Nicotiana tabacum L. plants was conducted using diluted wastewater to reduce the concentration of some chemical elements below the official accepted threshold values. Plants were grown in the greenhouse under controlled conditions for 21 days and irrigated with diluted HTL-WW every 24 hours. Soils and plants were sampled every seven days to evaluate, over time, the effect of wastewater irrigation both on soil microbial populations, through high-throughput sequencing, and plant growth parameters, through the measurement of different biometric indices. Metagenomic results highlighted that, in the HTL-WW treated rhizosphere, the microbial populations shifted via their mechanisms of adaptation to the new environmental conditions, establishing a new balance among bacterial and fungal communities. Identification of microbial taxa occurring in the rhizosphere of tobacco plants during the experiment highlighted that the HTL-WW application improved the growth of Micrococcaceae, Nocardiaceae and Nectriaceae, which included key species for denitrification, organic compounds degradation and plant growth promotion. As a result, irrigation with HTL-WW improved the overall performance of tobacco plants which showed higher leaf greenness and increased number of flowers compared to irrigated control plants. Overall, these results demonstrate the potential feasibility of using of HTL-WW in irrigated agriculture.